Influence of the feed rate and the lateral beam displacement on the joining quality of laser-welded copper-stainless steel connections - Weigl, M.; Schmidt, Michael (Physics Procedia, 2010)
The present article deals with the laser-welding of copper and stainless steel connections for applications in power electronics. Here, the particular demand for such dissimilar connections is caused by the increasing implementation of electronics in areas with contact to corrosive fluids, which copper cannot resist. In this context the influence of a lateral displacement of the laser beam and the feed rate on the metallurgical properties of the dissimilar materials' connection is highlighted. The effects of these parameters are discussed on the base of metallographic specimen, micro-hardness measurements and element analysis. © 2010 Published by Elsevier B.V.
Created from Fastlane, Scopus look-up
Keywords: Aluminium; Beam displacement; Copper; Dissimilar connection; Feed rate; Power electronics